A PENGARUH VARIASI KOMPOSISI CAMPURAN CARBON ARANG CANGKANG KEMIRI DAN NATRIUM KARBONAT TERHADAP KEKERASAN DAN KEAUSAN PADA MILD STEEL DENGAN PROSES PACK CARBURIZING - David Bintang Pradana; Agung Supriyanto; Afif Faishal (Pusat Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to determine the effect of variations in the composition of candlenut shell charcoal and sodium carbonate (Na?CO?) mixtures on mild steel’s hardness and wear resistance through the pack carburising process. The composition variations used were 60%:40%, 70%:30%, 80%:20%, and 90%:10% between coconut shell charcoal and Na?CO?. The carburising process was carried out at 930 °C to allow carbon diffusion to the steel surface, followed by Vickers hardness testing, Ogoshi wear testing, and surface chemical composition analysis using EDX. The results showed that pack carburising treatment significantly increased the hardness of the steel compared to the initial material, with the highest hardness (231.46 HV) obtained at a composition of 80% coconut shell charcoal and 20% Na?CO?. In addition, wear resistance also increased in the 90%:10% composition variation, with a specific wear value of 0.000029103 mm³/kg.m. EDX analysis indicated an increase in carbon content on the steel surface, proving the success of the carbon diffusion process.